Trends of ectopic pregnancies in Andaman and Nicobar Islands - Yadav, Anita; Prakash, Avinash; Sharma, Charu; Pegu, Bhabani; Saha, Mrinmoy Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Ectopic Pregnancy is a common life threatening emergency in the first trimester of pregnancy. Increase in incidence and impairment in fertility are the major concerns. The present study was undertaken to determine the incidence, clinical presentation, risk factors, diagnosis, management, maternal morbidity and mortality due to ectopic pregnancy in a tertiary care hospital. Methods: This cross-sectional, descriptive study was done over a period from January 2014 to October 2016. A total of 73 cases were admitted with the diagnosis of ectopic pregnancy. The following parameters: age, parity, risk factors, gestational age, clinical presentation, investigations, findings at surgery, morbidity and mortality associated with ectopic pregnancy was noted. Results: The incidence of ectopic pregnancy was 0.89%. The peak age of incidence was 25 to 34 years. Multiparous women were the most sufferers. Amenorrhea (93.15%), abdominal pain (87.67%) and vaginal bleeding (64.38%) were the frequent presenting complaints. Pelvic inflammatory disease (32.87%), history of previous caesarean section (26.02%) and history of abortion (13.69%) were the important risk factors. There were 90.41% patients with hemoglobin level less than 10 gm/dl, 8.21% of patients admitted with feature of shock. Majority (90.41%) of the cases were diagnosed through history and clinical examination. The commonest site of ectopic pregnancy was the ampulla (52.94%). Surgery by open method in the form of salpingectomy (72.05%) was the mainstay of treatment. Medical management was possible only in five cases. Morbidity included anemia (97.05%), urinary tract infections (11.76%) and wound infection (4.41%). No maternal mortality noted. Conclusions: Early presentation, high index of suspicion, early referral and timely intervention in the form of conservative or surgical treatment is the key to successful management of ectopic pregnancy.